75=3y

Simple and best practice solution for 75=3y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 75=3y equation:


Simplifying
75 = 3y

Solving
75 = 3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3y' to each side of the equation.
75 + -3y = 3y + -3y

Combine like terms: 3y + -3y = 0
75 + -3y = 0

Add '-75' to each side of the equation.
75 + -75 + -3y = 0 + -75

Combine like terms: 75 + -75 = 0
0 + -3y = 0 + -75
-3y = 0 + -75

Combine like terms: 0 + -75 = -75
-3y = -75

Divide each side by '-3'.
y = 25

Simplifying
y = 25

See similar equations:

| 25x-0=0 | | v=.33(3.14)r^2h | | 25x-0=500 | | x+65=3x-41 | | -26+-20= | | 2,5*(3-x)-0,2*(2x-5)=4 | | -5.4=-0.9m | | -5.4=-0.9 | | 4n-6=20 | | 3x-33=2x-26 | | 3x-(4-5x)=8x+3 | | 3q=19 | | -11x+2(3x+4)=-21 | | 8t=4 | | X/2+5=26 | | x+y/2=A | | 5+3z=6+4y-5-2y | | 8g=5g-6 | | 3h-5=16-3h+4(2h+3) | | x+6=5+x | | 5a+25=175 | | 3xy+12x= | | 31-(4g+2)=2(7-g)+5g | | -4(7-8m)=-27+5m | | 8(d+3)-10d=5d | | -7-x=-18 | | 4(10-p)+5p=47 | | 7-3f=4(3f-1)-2f | | x-9=6+3 | | h(t)=-24t^2+96t | | -2.5y+2.5z=-8.5 | | 25+.99=0+1.50 |

Equations solver categories